The Correlation between the Level of Health-Improving and Recreational Physical Activity and Family Well-Being - Olena Andrieieva; Dmytro Maltsev; Vitalii Kashuba; Igor Grygus; Evgeniia Zaharina; Andriy Vindyk; Dariusz Skalski; Serhii Hutsman (OVS LLC, 2022)
Study purpose. The purpose of the study was to assess the correlation between the level of health-improving and recreational physical activity and family well-being. Materials and methods. Theoretical analysis of data from special scientific and methodological literature, generalization, systematization, sociological methods, and mathematical statistics. A research among parents was conducted using online surveying through completing an online questionnaire created with Google Forms. The study involved 106 married couples. The average age of the respondents was 35.1±4.2 years. The vast majority of the studied families (95.1%) had up to two children (preschool and school age). Results. The respondents were divided into two clusters according to their level of motor activity. Cluster 1 included families with a low level of physical activity, and cluster 2 included those with an average level of physical activity.Depending on the level of physical activity, statistically significant (p < 0.05) differences were found between the families in terms of the following parameters: motivations for engaging in active leisure, amount of leisure time, level of knowledge and skills in organizing active leisure, reasons preventing participation in active leisure, etc. The families differed significantly (p < 0.05) in 23 categorical parameters. It was found that the families with different levels of physical activity did not differ in their desire to engage in winter recreational activities. Reasons preventing participation in health-enhancing and recreational physical activity programs were identified. A comparative analysis of the current state of family well-being revealed statistically significant (p < 0.05) differences in all studied parameters between the families with different levels of physical activity, i.e. the families with a proper level of physical activity had higher scores of satisfaction, well-being, and quality of life. Low indicators of family well-being indicated the rationale for such families to engage in active recreation and increase their level of health-enhancing and recreational physical activity. Conclusions. A relationship was identified between the level of health-enhancing and recreational physical activity and indicators of satisfaction, family well-being, and quality of life.